2011
DOI: 10.1038/eye.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and analysis of risk factors for age-related macular degeneration: 18-year follow-up data from the Speedwell eye study, United Kingdom

Abstract: Aims/Purpose To determine the prevalence of age-related maculopathy (ARM) and age-related macular degeneration (AMD) in men aged 65-83 years living in the Speedwell region of Bristol, United Kingdom and identify modifiable risk factors. Methods A total of 2348 men recruited to the Speedwell prospective cohort study in 1979 were followed up in 1997 with an eye questionnaire and had retinal photographs that were assessed using the International Classification System for ARM. Results In all, 934 men (66.8% respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 86 publications
0
31
0
Order By: Relevance
“…After reviewing the full-text articles, 21 articles (19 studies) were included in this meta-analysis (Figure 1) [8,9,10,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full-text articles, 21 articles (19 studies) were included in this meta-analysis (Figure 1) [8,9,10,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also compared pack‐years of smoking, and most of them confirmed an additive dose‐response effect . Even after quitting smoking, ex‐smokers still have a modestly increased risk of disease progression compared to never‐smokers, although this association is not always found . Quitting smoking reduces the risk of developing AMD and after 20 years cessation of smoking, risk probabilities of developing AMD seem to be comparable to that of non‐smokers .…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 98%
“…Evidence of studies using CRP values to predict disease progression in AMD are inconclusive. Five prospective studies found no relation between systemic CRP levels and AMD progression . There is one study which used a more precise measurement of CRP (high‐sensitivity CRP [hsCRP]) and found a positive relationship with the development of early AMD …”
Section: Molecular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, in 2002, age-related macular degeneration (AMD) and the juvenile-type macular degeneration (JMD) were the causes of blindness and low-vision in 8.7% of the 160 million cases worldwide. 1 In recent reports, AMD prevalence ranged from approximately 3 -12% [2][3][4][5][6][7][8][9] , while the prevalence of JMD was 0.03%. 10 In Europe, the retinal pathologies underlying AMD and JMD are listed in the top five of causes of visual loss in both children and adults.…”
Section: Introductionmentioning
confidence: 99%